Predation of citrus red mite (Panonychus citri) by Stethorus sp and Agistemus longisetus - Jamieson, L.E.; Chhagan, A.; Charles, J.G. (New Zealand Plant Protection, 2008)
The ladybird Stethorus sp and the predatory mite Agistemus longisetus are the most abundant natural enemies found with high populations of citrus red mite (CRM) (Panonychus citri) To enable the continued use of pesticides that may be toxic to one or both of these predators knowledge of their roles in regulating CRM populations is required In laboratory bioassays both natural enemies alone and in combination reduced the number of eggs and immature CRM However A longisetus alone did not reduce the number of CRM adults as effectively as Stethorus sp alone or in combination In a glasshouse trial predation by a combination of Stethorus sp and A longisetus reduced CRM populations faster than predation by Stethorus sp alone Stethorus sp is the more effective of the two common CRM natural enemies at reducing high populations of CRM but the combined predation of the two predators may be complementary in highly dispersed populations where there are a large number of leaves with few eggs